Physiotherapy practices for patients undergoing coronary artery bypass grafting: a cross- sectional study - Muhammad Khan; Shaikh Nabi Bukhsh Nazir; Aftab Ahmed Mirza Baig (Journal of the Pakistan Medical Association, 2020)
Objective: To evaluate physiotherapy practices in the rehabilitation of patients undergoing coronary artery bypass grafting. Methods: The cross-sectional study was conducted from October 2016 to January 2017 in cardiac care units of two private and two government hospitals in Karachi, and comprised physiotherapists dealing with patients undergoing coronary artery bypass grafting. Data was collected using a modified and validated version of ‘tucker q’ questionnaire. Data was analysed using SPSS 21. Results: Of the 101 physiotherapists, 60(59.4%) were females and 41(40.6%) were males. The overall work experience was 4.89+2.08 years. Of the total, 60(59.4%) physiotherapists used air suctioning in preoperative physiotherapy practices. Relaxation techniques were used by 86(85.10%) professionals and postural drainage by 85(84.20%), while breathing exercises were used by 65(64.4%) subjects in postoperative physiotherapy practices. Conclusion: Physiotherapists were found to be more or less keeping abreast with advances made regarding managing patients undergoing cardiac artery bypass grafting. Key Words: Coronary artery surgery, Heart surgery, Cardiac rehabilitation, Physical therapy, Breathing exercises, Postoperative care. Continuous...